Authoritarian Environmentalism and Sustainable Development Explaining China's Ecological Civilization Success and Its Structural Limits for the Post-Colonial Global South - Arif Darmawan; Elpeni Fitrah; Renny Miryanti; Soni Martin Anwar; Kiky Srirejeki; Aryuni Yuliantiningsih; Ulil Afwa; Hanifa Pascarina (Global South Review, 2025)
In response to the escalating global environmental crisis, China has initiated "Ecological Civilization," a distinctive state-led approach to environmental sustainability and harmonious development. Rooted in Marxist ecological thought and traditional Chinese philosophies emphasizing human-nature harmony, this initiative diverges from Western models and is enshrined in China's constitution and national policies. This essay provides an expert-level analysis of Ecological Civilization, examining its core principles, theoretical foundations (including Taoist and Confucian influences and modern sustainability concepts), and implementation within China. It assesses both successes—such as large-scale afforestation (e.g., Three-North Shelter Forest Program, Grain to Green Program), biodiversity conservation through protected areas and Ecological Conservation Redlines, and advancements in green energy transition —and failures, including persistent pollution, enforcement challenges, and socio-ecological impacts of large infrastructure projects. The analysis explores the strong synergies between Ecological Civilization and the UN Sustainable Development Goals (SDGs), particularly SDG 7 (Energy), SDG 11 (Cities), SDG 13 (Climate Action), SDG 15 (Life on Land), and SDG 12 (Sustainable Consumption). Considering the sustainability efforts and unique challenges faced by Global South countries, this essay distills valuable insights from China's experience. Key lessons highlight the importance of strong state leadership, quantitative targets, large-scale ecological restoration, and green technology innovation, while emphasizing the crucial need for context-specific adaptation, stakeholder engagement, and equitable strategies for the Global South